2007
DOI: 10.1038/ncb1641
|View full text |Cite
|
Sign up to set email alerts
|

Akt phosphorylation regulates the tumour-suppressor merlin through ubiquitination and degradation

Abstract: The neurofibromatosis-2 (NF2) tumour-suppressor gene encodes an intracellular membrane-associated protein, called merlin, whose growth-suppressive function is dependent on its ability to form interactions through its intramolecular amino-terminal domain (NTD) and carboxy-terminal domain (CTD). Merlin phosphorylation plays a critical part in dictating merlin NTD/CTD interactions as well as in controlling binding to its effector proteins. Merlin is partially regulated by phosphorylation of Ser 518, such that hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 28 publications
6
80
0
2
Order By: Relevance
“…When serine 518 is dephosphorylated by the myosin phosphatase MYPT-1-PP1d, the tumor suppressor function of merlin is activated, inhibiting the Ras signaling pathway and leading to growth arrest (Morrison et al, 2001;Jin et al, 2006). Recently, also two Akt phosphorylation sites, threonine 230 and serine 315, were identified in the N terminus of merlin (Tang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…When serine 518 is dephosphorylated by the myosin phosphatase MYPT-1-PP1d, the tumor suppressor function of merlin is activated, inhibiting the Ras signaling pathway and leading to growth arrest (Morrison et al, 2001;Jin et al, 2006). Recently, also two Akt phosphorylation sites, threonine 230 and serine 315, were identified in the N terminus of merlin (Tang et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…extracellular signals or stress is a common mechanism "priming" certain proteins for subsequent recruitment of degradation machinery (29,30). We investigated whether EGF could induce phosphorylation of EPLIN in ARCaP E cells, which may be a prerequisite for ubiquitination and degradation of EPLIN.…”
Section: Egf Induces Serine Phosphorylation and Eplin Turnover Througmentioning
confidence: 99%
“…Tumor suppressors are frequently degraded in cancer cells through polyubiquitination-mediated mechanism, including p53 (Maki et al, 1996), PTEN (Trotman et al, 2007;, and merlin (Tang et al, 2007). To investigate whether Ebp1 can also be modified by polyubiquitination, we cotransfected HA-ubiquitin into HEK293T cells with GST-tagged p42 and p48, followed by a proteasome inhibitor MG132 treatment for 4 h. GST-pull-down assay revealed that p42 but not p48 was potently polyubiquitinated, which was enhanced by MG132 treatment ( Figure 1A).…”
Section: Ebp1 P42 But Not P48 Isoform Is Ubiquitinatedmentioning
confidence: 99%